Tron legacy - Kosinski, Joseph; Horowitz, Adam.; Kitsis, Eddy.; Bridges, Jeff, 1949-; Hedlund, Garrett, 1985-; Wilde, Olivia; Boxleitner, Bruce; Sheen, Michael; Bailey, Sean, 1970-; Silver, Jeffrey; Lisberger, Steven; Daft Punk (Musical group); et al. ([Burbank, Calif.] : Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2011)
When Flynn, the world's greatest video game creator, sends out a secret signal from an amazing digital realm, his son discovers the clue and embarks on a personal journey to save his long-lost father. With the help of the fearless female warrior Quorra, father and son venture through an incredible cyber universe and wage the ultimate battle of good versus evil.
Based on characters created by Steven Lisberger and Bonnie MacBird.
DVD release of the 2010 motion picture.
Special features: First look at Tron: uprising; visualizing Tron; installing the cast.
Music, Daft Punk ; editor, James Haygood ; director of photography, Claudio Miranda.
Jeff Bridges, Garrett Hedlund, Olivia Wilde, Bruce Boxleitner, Michael Sheen.
MPAA rating: PG; for sequences of sci-fi action violence and brief mild language.
Keywords: Computer hackers -- Drama; Fathers and sons -- Drama; Science fiction films; Action and adventure films; Animated films; Film sequels; Fiction films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Animated films -- United States; Feature films -- United States